From training to professionalization in cultural action: Realities and future prospects in public policies (Xerf@ Project in Galicia) - Pose-Porto, Héctor; Caride, José Antonio (Education Policy Analysis Archives, 2022)
This article contributes to the analysis of different circumstances involved in the formation and professionalisation of public cultural action in Galicia. Without ignoring important regulatory and strategic advances made in recent decades, the needs and demands that emerge from these advances give light to the decisions for future local cultural policies. In the design and execution of programs and initiatives, politicians and technicians associated with municipal cultural management play key roles, as guarantors of the rights of citizens to participate in the creation and enjoyment of the cultural assets of the community. From this perspective, some achievements linked to the theoretical-conceptual, methodological, and empirical approaches of Proxecto Xerf@ are presented with a diagnostic and prospective vision. Based on various procedures to collect and analyze information, the results demonstrate that cultural action professionals need improved initial and continuous training, along with improved processes for their incorporation, performance, and socio-professional and work-related promotion.